Nurses' leadership self-efficacy, motivation, and career aspirations. Issue 1 (8th December 2017) - Cziraki, Karen; Read, Emily; Spence Laschinger, Heather K.; Wong, Carol
Abstract : Purpose: This paper aims to test a model examining precursors and outcomes of nurses' leadership self-efficacy, and their aspirations to management positions. Design/methodology/approach: A cross-sectional survey of 727 registered nurses across Canada was conducted. Structural equation modelling using Mplus was used to analyse the data. Findings: Results supported the hypothesized model: χ 2 (312) = 949.393; CFI = 0.927; TLI = 0.919; RMSEA = 0.053 (0.049-0.057); SRMR 0.044. Skill development opportunities ( ß = 0.20), temporary management roles ( ß = 0.12) and informal mentoring ( ß = 0.11) were significantly related to nurses' leadership self-efficacy, which significantly influenced motivation to lead ( ß = 0.77) and leadership career aspirations ( ß = 0.23). Motivation to lead was significantly related to leadership career aspirations ( ß = 0.50). Practical implications: Nurses' leadership self-efficacy is an important determinant of their motivation and intention to pursue a leadership career. Results suggest that nurses' leadership self-efficacy can be influenced by providing opportunities for leadership mastery experiences and mentorship support. Leadership succession planning should include strategies to enhance nurses' leadership self-efficacy and increase front-line nurses' interest in leadership roles. Originality value: With an aging nurse leader workforce, it is important to understand factors influencing nurses' leadership aspirations to develop and sustain nursing leadership capacity. This research study makes an important contribution to the nursing literature by showing that nurses' leadership self-efficacy appears to be an important determinant of their motivation to lead and desire to pursue a career as a nurse leader.